2021
DOI: 10.1016/j.asoc.2021.107611
|View full text |Cite
|
Sign up to set email alerts
|

Particle swarm optimization of partitions and fuzzy order for fuzzy time series forecasting of COVID-19

Abstract: Major hyperparameters which affect fuzzy time series (FTS) forecasting are the number of partitions, length of partition intervals in the universe of discourse, and the fuzzy order. There are very few studies which have considered an integrated solution to optimize all the hyperparameters. In this paper, we strive to achieve optimum values of all three hyperparameters for fuzzy time series forecasting of the COVID-19 pandemic using the Particle Swarm Optimization (PSO) algorithm. We specifically propose two te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Ceylan ( 2021 ) proposed a hybrid model based on GM(1,1) and a PSO and utilized it to forecast the cumulative case number of COVID-19 in Germany, Turkey, and USA. Kumar and Susan ( 2021 ) considered fuzzy time-series and PSO to forecast the COVID-19 pandemic. Li et al ( 2021 ) identified new infected COVID-19 patients in terms of small data and poor information using the improved GM(1,1) model.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…Ceylan ( 2021 ) proposed a hybrid model based on GM(1,1) and a PSO and utilized it to forecast the cumulative case number of COVID-19 in Germany, Turkey, and USA. Kumar and Susan ( 2021 ) considered fuzzy time-series and PSO to forecast the COVID-19 pandemic. Li et al ( 2021 ) identified new infected COVID-19 patients in terms of small data and poor information using the improved GM(1,1) model.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“… [20] evoked the COVID-19 impact on ambulances’ turnaround time and proposed a two-stage machine learning methodology to solve the problem in a given time and hospital. Kumar and Susan [21] proposed a novel fuzzy time series forecasting with the particle swarm optimization to handle the emergency ambulance dispatch problem.…”
Section: Related Workmentioning
confidence: 99%
“…(5) end for (6) assign linguistic variable to all historical data according to the belonging of data to their respective subinterval (7) define FLR and FLRG (8) defuzzify the historical data by using (21) for known linguistic variable (9) determine the forecasted value by using (22) for unknown linguistic variable (10) return forecasted values Both phases I and II are depicted through flow chart in Figure 1.…”
Section: Phase-iimentioning
confidence: 99%
“…Mahmoudi et al [7] compared the COVID-19 spread rate in high-risk countries using time series and fuzzy clustering algorithms. Kumar and Susan [8] proposed two approaches, named as, nested FTS-PSO and exhaustive search FTS-PSO to forecast the COVID-19. Elleuch et al [9] proposed method for real time forecasting of COVID-19 patients health based on artificial neural networks and fuzzy interval mathematical modeling.…”
Section: Introductionmentioning
confidence: 99%